(untitled) (Research, Society and Development, 2021)
This article aims to present how Grounded Theory (GT) can be applied in research in the field of higher education. GT is a methodology widely used in health, administration, and psychology, and is recognized on the international scene. In Brazil, in the field of education it is little used, and this becomes the differential of this research. Thus, the following questions arise What reflections are in evidence about the university in today’s society? A qualitative exploratory research was carried out using as methodology the constructivist GT and the use of the software My-Sae and Gephi to support data collection and analysis. The results demonstrate the usefulness of GT in the search, analysis, and production of data and categories. The conclusion is that it can be quite useful if applied to the field of education, since its purpose is propositional and reflexive, besides broadening the view on higher education issues.